Effects of sorghum grain and sorghum dried distillers grains with solubles on the composition, quality and sensory attributes of ground pork - Skaar, Garrett Richard (Kansas State University, 2011)
A total of 48 carcasses were taken from a larger trial using 288 pigs (PIC TR4 × 1050, initially 58.9 kg) in a 73 d feeding study to determine the effects of sorghum dried distillers grains with solubles (S-DDGS) in sorghum- or corn-based diets on ground pork quality. The dietary treatments included: sorghum-based diets with 0, 15, 30, or 45% SDDGS, a sorghum-based diet with 30% corn DDGS (C-DDGS) and a corn-based diet with 30% C-DDGS. Shoulders from 24 barrow and 24 gilt carcasses were ground and evaluated for proximate and fatty acid composition, iodine value (IV), objective color, thiobarbituric acid-reactive substances (TBARS), and sensory attributes. No finishing diet × gender interaction was detected for composition, fatty acid profile, color or TBARS (P > 0.05). Pork from gilts contained less fat and more moisture (P < 0.001), was less saturated with a greater IV and total percentage of PUFA (P < 0.01), and also had a lower L* value (P < 0.001) and higher a* value (P = 0.006) than pork from barrows. Gender did not affect total color change ( E) from 0 to 120 h (P = 0.30), TBARS (P = 0.08), or sensory attributes (P ≥ 0.32). Finishing diet had no affect on total fat, moisture, or protein composition (P ≥ 0.18). Increasing S-DDGS resulted in a linear (P < 0.001) decrease in SFA and MUFA and an increase (P < 0.01) in PUFA and ground pork IV. Pork from pigs fed 30% S-DDGS had a greater percentage of MUFA (P = 0.01) and a lower percentage of PUFA (P > 0.006) and reduced IV (P = 0.03) compared to pork from pigs fed the sorghum-based diet with 30% C-DDGS. Diet did not affect TBARS (P = 0.37) or L*, a*, or b* values (P ≥ 0.11) but was shown to influence E (P = 0.01) with pork from pigs fed sorghum grain and 30% S-DDGS having less total change than all other treatments. It is concluded that consumers will not be able to differentiate ground pork from pigs fed DDGS and that feeding sorghum grain and S-DDGS can be done without affecting ground pork quality.
Keywords: Dried distillers grains with solubles; Pork; Sorghum; Meat color; Sensory; TBARS; Agriculture, General (0473); Animal Sciences (0475); Food Science (0359)